Evaluation of Silver European EEL (anguilla anguilla) for the implementation of an Effective EEL Management plan in Mediterranean Coastal Lagoons - Brunelli, Federico <1975> (Alma Mater Studiorum - Università di Bologna, 2012)
This thesis presents SEELF (Sustainable EEL fishery) Index, a methodology for evaluation of European eel (Anguilla anguilla) for the implementation of an effective Eel Management Plan, as defined by EU Regulation No.1100/2007. SEELF uses internal and external indices, age and blood parameters, and selects suitable specimen for restocking; it is also a reliable tool for eel stock management. In fact, SEELF Index, was developed in two versions: SEELF A, to be used in field operations (catch&release, eel status monitoring) and SEELF B to be used for quality control (food production) and research (eel status monitoring). Health status was evaluated also by biomarker analysis (ChE), and data were compared with age of eel. Age determination was performed with otolith reading and fish scale reading and a calibration between the two methods was possible. The study area was the Comacchio lagoon, a brackish coastal lagoon in Italy, well known as an example of suitable environment for eel fishery, where the capability to use the local natural resources has long been a key factor for a successful fishery management. Comacchio lagoon is proposed as an area where an effective EMP can be performed, in agreement with the main features (management of basins, reduction of mortality due to predators,etc.) highlighted for designation of European Restocking Area (ERA). The ERA is a new concept, proposed as a pillar of a new strategy on eel management and conservation. Furthermore, the features of ERAs can be useful in the framework of European Scale Eel Management Plan (ESEMP), proposed as a European scale implementation of EMP, providing a more effectiveness of conservation measures for eel management.